Album Organisationsform narrativer Kohärenz - Kramer, Anke (Wallstein Verlag, 2013)
The twenty-tow contributions in this transnational and interdisciplinary volume delve into the material, symbolic and aesthetic dimensions of the album format using approaches from the fields of cultural studies, literary studies and media studies. This Publication unites perspectives from English, American, German, Romance, Slavic, archive and film studies, history, art history, musicology and philosophy to explore this culturally significant ,networking' medium.The starting point for all of the contributions in the publication is the album format, which, with ist inscriptions and non-verbal semantics, can integrate, represent and symbolically reproduce all forms of media and culture. The volume's main interest is the interconnectedness: The album has the innate abily to unify the most diverse subject areas. Representation, mobility, migration and memory, multiculturalism and the formation of communities, materiality and the culture of things, the discourse of friendship, family history, generational narratives, and transmedia experimentation in remolding genres and art forms all have a place in the album, as it can transform anything into one coherent aesthetic system.